PENDEKATAN KONSELING DALAM PENDIDIKAN JASMANI DAN OLAHRAGA - ibrahim, rusli (Jurnal Kepelatihan Olahraga, 2011)
Counseling approach in physical education and sport is a field of applied psychology of sport. It is most important and useful to enhance the performance in physical education and sport and to promote the well-being of students or athletes, coaches, and physical educators in schools. Therefore, the understanding of the role of physical education and sport in human development is necessity in planning of counseling approach for students or athletes.There is a premise that participation in physical education and sport activities prepares students or athletes for later adult roles. Physical education and sport teaches young people how to live by rules, to possess the social behavior according to social and cultural values, work hard to achieve goals, and play and interact with others. Indeed, in the other perspective that physical education and sport activities are indirectly influence toward the character building of students and athletes.Counseling programs are apparently useful to assist career development; and counseling injured students or athletes; and while students or athletes are being in transition period from adolescent to adult age. There are three main aspects of career development process, namely (1) Self exploration; (2) Environment or Career exploration; and (3) Career implementation.